Development and fabrication of co-axially electrospun biomimetic periosteum with a decellularized periosteal ECM shell/PCL core structure to promote the repair of critical-sized bone defects. (1st April 2022) - Li, Shuyi; Deng, Rongli; Zou, Xuenong; Rong, Qiong; Shou, Jiali; Rao, Zilong; Wu, Wanqiu; Wu, Gang; Quan, Daping; Zhou, Miao; Forouzanfar, Tim
Abstract: Periosteum is crucial to the initial healing of bone defects because it provides a stable periosteum-specific microenvironment and abundant osteogenic cells towards bone repair. However, the usage of autologous periosteum is restricted for limited availability. Xenogeneic decellularized periosteum (DP) preserves periosteum-specific cues but the hardly-controlled physicochemical properties render it inconvenient to use widely. Our study aimed to fabricate a tissue-engineered periosteum (TEP) with a continuous periosteum-specifically bioactive surface and tailored physicochemical properties by co-axial electrospinning of poly(ε-caprolactone) (PCL)/periosteal decellularized extracellular matrix (dECM) to promote bone defects healing. Before use, DP was confirmed for effective removal of residual DNA and well preservation of biological components, e.g., collagen and glycosaminoglycans. After optimization of fabrication processes, PCL/dECM co-axially electrospun membrane (PEC) bore an exquisite core-shell structure, which was effectively equipped with composite advantages of dECM and PCL. Notably, PEC stood out in terms of tensile strength and long-term durability within a physiological environment compared to that of the dECM uniaxial electrospun membrane (ECM). Besides, PEC exhibited remarkably better cell proliferation, migration, bio-mineralization, and osteogenic properties as compared to that of the electrospun PCL membrane. Moreover, PEC-TEP could significantly enhance the recovery of critical-sized bone defects in rats than that of PCL-TEP. To the best of our knowledge, biomimetic PEC-TEP was fabricated and used for the first time to repair bone defects. This novel strategy is promising to fabricate a dECM-based advanced membrane for tissue engineering. Graphical abstract: Image 1